Exploring the Pathogen Diagnosis and Prognostic Factors of Severe COVID-19 Using Metagenomic Next-Generation Sequencing: A Retrospective Study: ESR1 and MMP3 Profiles Predict Prostate Cancer Recurrence Risk - Zeng, Weizhong; Liang, Yanchao; He, Xiaoyuan; Chen, Fangwei; Xiong, Jiali; Wen, Zhenhua; Tang, Liang; Chen, Xun; Zhang, Juan (Journal of Medical Biochemistry, 2024)
Background: This study aimed to identify pathogens and factors that predict the outcome of severe COVID-19 by utilizing metagenomic next-generation sequencing (mNGS) technology.Methods: We retrospectively analyzed data from 56 severe COVID-19 patients admitted to our hospital between December 2022 and March 2023. We analyzed the pathogen types and strains detected through mNGS and conventional microbiological testing and collected general patient information.Results: In this study, 42 pathogens were detected using mNGS and conventional microbiological testing. mNGS had a significantly higher detection rate of 90.48% compared to 71.43% for conventional testing (P=0.026). A total of 196 strains were detected using both methods, with a significantly higher detection rate of 70.92% for mNGS compared to 49.49% for conventional testing (P=0.000). The 56 patients were divided into a survival group (33 cases) and a death group (23 cases) based on clinical outcomes. The survival group had significantly lower age, number of pathogens detected by mNGS, number of pathogens detected by conventional testing, APACHE-II score, SOFA score, high-sensitivity troponin, creatine kinase-MB subtype, and lactate dehydrogenase compared to the death group (P
Keywords: Pathogens; mNGS; Conventional Pathogen Test; APACHCE-II; SOFA